2016
DOI: 10.18203/2320-1770.ijrcog20163848
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to non-compliance to routine ante-natal haematinics among pregnant women attending ante-natal clinic in University of Maiduguri Teaching Hospital, Borno, Nigeria

Abstract: Background: This study was carried out on factors contributing to non-compliance to routine ante-natal haematinics among pregnant women attending ante-natal clinic in University of Maiduguri Teaching Hospital. Descriptive research design in which Yaro Yamen's formular was used to calculate the sample size of 130. The objectives of the study were: to identify types of haematinics and duration of intake during ante natal care, to determine the factors contributing to non-compliance of haematinics and to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…In the current study, we report a compliance rate of about 63%, 63% and 58% for FA, FS and MTV, respectively. This puts the average of these rates at 61% and clearly higher than the 48% reported among Nigerian women in a similar setting . However, the finding is consistent with studies conducted in India which reported the overall compliance with iron‐folic acid tablets as around 65% .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the current study, we report a compliance rate of about 63%, 63% and 58% for FA, FS and MTV, respectively. This puts the average of these rates at 61% and clearly higher than the 48% reported among Nigerian women in a similar setting . However, the finding is consistent with studies conducted in India which reported the overall compliance with iron‐folic acid tablets as around 65% .…”
Section: Discussionsupporting
confidence: 85%
“…Worldwide, anaemia in pregnancy is estimated to be about 38%, with the Africa region estimates being around 46% . Mothers with untreated anaemia have been amply demonstrated to give birth to babies who are premature, have a low birth weight, have less mental ability and have increased risk of infection, heart and lung problems . Neural tube defects that manifest as hydrocephalus, spinal bifida and encephalocele have also been linked to low intake of folic acid, an important haematinic …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated a poor level of compliance among pregnant women, as less than half always bought their routine medications and used them as prescribed. Compliance refers to the extent to which the pregnant woman follows medical prescription and this has been a major issue in micronutrient supplementation in pregnancy 13 , 18 . Although a little less than two-thirds of the respondents were either primiparous or with one child and the majority also had tertiary education, it is rather surprising that compliance was still poor, as they were expected to keep to their prescription being new to the pregnancy experience.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was reported that the compliance of pregnant women to antenatal medication in developing countries was low (28.7%) 12 . It has also been found that about 58 million women in developing countries are anaemic during pregnancy and this situation was likely the result of non-compliance of the pregnant women with antenatal medication 11 , 13 . Additionally, studies 13 , 14 have suggested that babies born to mothers who do not comply with the taking of antenatal medications are more likely to be born prematurely (before the 37th week of pregnancy), have a low birthweight, have problems with iron levels and a poorer performance in mental ability tests; they are also at increased risk of infection, heart and lungs problems, restless leg syndrome, etc.…”
Section: Introductionmentioning
confidence: 99%